European Union's co-operation with small island developing states in the framework of the Barbados Programme of Action (European Commission BrusselsBE, 1999)
Looks at European Union's aid and then concentrates on its actions in individual island states as well as its regional activities. Focuses on EU's development cooperation actions in SIDS under the 14 categories of the Barbados Programme of Action.
DC